Relationship Between Personality Types in MBTI and Dream Structure Variables - Zhao, Chuanwen; Wang, Jiaxi; Feng, Xiaoling; Shen, Heyong (Frontiers in Psychology, 2020)
This study aimed to explore relationships between personality type variables and dream structure variables. In the questionnaire experiment (N=410), we investigated associations between different personality variables in the Myers-Briggs Type Indicator questionnaire (MBTI) and various aspects of dreams in the Mannheim Dream questionnaire (MADRE). The MBTI has four dimensions. In the Extroversion/Introversion (E/I) dimension, I types dreamt more of emotional intensity and passive emotions than E types. Besides, I types may get more distressing in nightmares than E types. E types were more frequent to share their dreams with others. In the Sensation/Intuition (S/N) dimension, N types had a more positive attitude towards dreams and can get more novel ideas and helps from their dreams than S types. In the dream diary experiment (N=47), we investigated whether the S/N dimension may influence waking events' incorporating into dreams. External judges decoded paired waking events and dream reports. N types had more metaphorical incorporation than S types. More specifically, N types had more metaphorical expressions in their dreams than S types. This result may be due to the different characteristics between S types and N types. It may give support for the dream continuity hypothesis.